P-015 Long-term results of angioplasty using stent-retrievers for cerebral vasospasm in subarachnoid hemorrhage patients. (23rd July 2017) - Kwon, H; Lee, Y; Koh, H
Abstract : Introduction/Purpose: To report our long-term results of mechanical angioplasty using stentrievers for recurred symptomatic cerebral vasospasm in subarachnoid hemorrhage patients. Materials and Methods: We retrospectively reviewed medical records and radiological images of 7 patients who developed delayed vasospasm following subarachnoid hemorrhage and showed recurrence after initial angioplasty using intra-arterial vasodilator infusion from 2014 to 2017 at our institution. For those patients, we temporarily deployed a stentriever in the spastic branches for 3 min for mechanical vasodilation under general anesthesia and full heparinization. Three available stentrievers (Solitaire, Trevo, Revive) were used. We evaluated the clinical and radiological outcomes including recurrence rates and feasibility. Results: A total of 39 stentriever-angioplasties were attempted for proximal or distal vessels. Deliveries and deployments of the stentrievers to the targeted spastic segments were feasible in all of the procedures before the intra-arterial infusion of vasodilator. Instant angiographical vasodilations were acquired in 33 (85%) vessels after retrieval of stentrievers. Follow-up images showed no significant recurrence of vasospasm in the vessels dilated by the stentrievers. Neurological improvements were noted in 6 (86%) patients after the procedures which include subsequent intra-arterial vasodilator infusion. One thrombotic occlusion of branch was recanalized with intra-arterial Tirofiban infusion. Temporary aggravation of vasospasm in the supraclinoid ICA which was thought to be caused by microcatheter irritation was relieved with the same procedure. One case of wire-induced distal vessel injury was trapped with detachable coils without further neurological detriment of the patient. No angiographical abnormality was found in the stentriever-deployed spastic vessels (12/39, 31%) at long-term follow-up angiograms (3 patients, mean 18.6 months). Conclusion: Mechanical angioplasty using stent-retrievers for the delayed symptomatic vasospasm in the subarachnoid hemorrhage patients can be a feasible option especially for the recurred cases after chemical only angioplasty. Disclosures: H. Kwon: None. Y. Lee: None. H. Koh: None.